Membangun Prestasi Belajar dengan Membaca - Eny Supriati (IAIN Ponorogo, 2009)
Learning is an attemp to acquire cleverness and knowledge. It is also similar to training. In other words, it means behavior change or respond which is initiated by experience. behaviour change from dissability to do something to ability to do something is called learning. the common understanding, whish is followed by lecturers and has to be accepted by student. The success or achievement of learning is measured by how to the student can demonstrate well taht they are able to enunciate clearly all knowledge wanted by the lecturer. It what has been enunciated is not appropriate with the lecture desire, its means that the student has not studied yet.